Tumor cell-specific Serpin A1 expression in vulvar squamous cell carcinoma - Maria Lagerstedt; R. Huotari-Orava; R. Nyberg; L. Nissinen; M. Farshchian; S.-L- Laasanen; E. Snellman; J. U. Mäenpää; V.-M. Kähäri (Springer Berlin Heidelberg, 2025)
Purpose
The two main etiological factors for vulvar squamous cell carcinoma (vSCC) are the vulvar dermatosis lichen sclerosus (LS) and high-risk human papillomavirus (hrHPV). Serpin A1 (α1-antitrypsin) is a serine protease inhibitor, which plays a role in the tumorigenesis of various cancer types. The aim of the study was to evaluate the expressions of Serpin A1 in LS, premalignant vulvar lesions, and vSCC using immunohistochemistry (IHC) and serum analysis, and to compare Serpin A1 stainings to the tumor markers p53 and p16.
Methods
In total, 120 samples from 74 patients were studied with IHC for Serpin A1, p53 and p16: 18 normal vulvar skin, 53 LS, 9 premalignant vulvar lesions (dVIN/HSIL) and 40 vSCC samples. Serum concentrations of Serpin A1 were analyzed from 30 LS, 44 vSCC and 10 control patients. Expressions were compared to clinical data.
Results
Tumor cell-specific Serpin A1 overexpression was detected in 88% of vSCC samples, independent of the etiology. The intensity of Serpin A1 expression was significantly higher in vSCC than in healthy vulvar skin, LS, or premalignant vulvar lesions. Serpin A1 showed an association with p53 positivity. No difference in overall survival was found between Serpin A1-, p53-, or p16-positive vSCC patients. Serum concentrations of Serpin A1 were equal in the LS, vSCC, and control groups.
Conclusion
Tumor cell-specific Serpin A1 overexpression is a potential biomarker in vSCC.